Nowe prawno-instytucjonalne, ekonomiczne, społeczne i technologiczne ograniczenia wykorzystania niekonwencjonalnych nośników energii na początku XXI wieku - Becla, Agnieszka; Czaja, Stanisław (New Legal-Institutional, Economic, Social and Technological Limitations of Using Unconventional Carriers of Energy at the Beginning of the 21st Century, 2009)
The authors present the growing use of energy in present civilization and introduce threats connected with this phenomenon. They pay attention to a role of unconventional energy. They also explain a notion and range of this energy and talk over the form of individual energy carriers influence on natural environment. The basic barriers of unconventional energy developing in Poland are one of important elements of this study. They are economic-financial and structural, social and mental, legal and institutional, informative and technical or technological and infrastructural barriers. Presenting the barriers, the authors' attention is paid to actions supporting the development of unconventional power industry. The recommendations for Polish energy policy close the article.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 235-253